2005
DOI: 10.1039/b418580c
|View full text |Cite
|
Sign up to set email alerts
|

Artificial photochemical nitrogen cycle to produce nitrogen and hydrogen from ammonia by platinized TiO2 and its application to a photofuel cell

Abstract: Photochemical artificial nitrogen cycle was reported to produce dinitrogen and dihydrogen by photodecomposing ammonia with platinized TiO2, and its application to a photofuel cell with a nanoporous TiO2 film electrode, a new concept of a fuel cell to photochemically produce electricity and H2 from ammonia, was proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 7 publications
0
32
0
Order By: Relevance
“…The corresponding Pt and Rh oxide components were identified in the O 1s spectra at 530,5 eV (not shown). Fierro et al [36] reported for the PtRh/C (90: 10) phase binding energies of 71.1 eV for Pt 4f 7/2 and 309.4 eV for Rh 3d 5/2 . Therefore, it cannot be excluded that the Rh 3d 5/2 component close to 310 eV could be related to PtRh alloy.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The corresponding Pt and Rh oxide components were identified in the O 1s spectra at 530,5 eV (not shown). Fierro et al [36] reported for the PtRh/C (90: 10) phase binding energies of 71.1 eV for Pt 4f 7/2 and 309.4 eV for Rh 3d 5/2 . Therefore, it cannot be excluded that the Rh 3d 5/2 component close to 310 eV could be related to PtRh alloy.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, ammonia is also one of the most concerning industrial wastes because its large-scale production, being the second largest chemical produced all over the world [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of electrons by the particles of the metal not only helps to overcome the potential barrier of many reduction reactions but also reduces the probability of electron-hole recombination in the volume of the semiconductor nanoparticle. Increase in the degree of primary separation of charges and acceleration of reactions involving holes from the valence band have been observed in the case of nanocomposites based on Pt, Ir, and TiO 2 nanoparticles [117] and also in TiO 2 /Au [117][118][119][120][121][122][123], TiO 2 /Pt [124][125][126], TiO 2 /Pd [127], TiO 2 /Ag [128][129][130][131][132][133][134], ZnO/Au [135], CdS/Au [136], and Fe 2 O 3 /Au [137] nanocomposites. The quantum yield of the photocatalytic release of molecular hydrogen from aqueous solutions with the participation of the nanoparticles of practically all photoactive semiconductors except ZnS [9,138] and binary semiconductor composites based on it [139][140][141] in the absence of metal is close to zero.…”
Section: Photocatalytic Reactions Involving Binary Metal-semiconductomentioning
confidence: 99%
“…In the previous report, we found that NH 3 is decomposed into N 2 and H 2 at the almost theoretical 1/3 molar ratio under Ar atmosphere, while producing photocurrent by using the same cell system [9]. It should be noted here that the J-V characteristics of the N 2 /H 2 -producing system reported earlier by our group operated under Ar atmosphere were …”
Section: Resultsmentioning
confidence: 87%
“…5a, b exhibited clear photoanodic currents, both being saturated around 3 mA cm -2 , which demonstrates that the O 2 concentration in air is sufficient for the O 2 reduction at the Pt cathode for the liquid methanol most probably due to the high solubility of O 2 in methanol that is about one order higher than that in water. It is important in our BPCC that organic compounds can be entirely decomposed into CO 2 (and N 2 ) as reported earlier [6][7][8][9]. The methanol decomposition (6 e -process) is represented by the Eqs.…”
Section: Resultsmentioning
confidence: 99%